2021
DOI: 10.3390/molecules26082164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3FTx Protein Fraction from Naja ashei Venom on the Model and Native Membranes: Recognition and Implications for the Mechanisms of Toxicity

Abstract: Three-finger toxins are naturally occurring proteins in Elapidae snake venoms. Nowadays, they are gaining popularity because of their therapeutic potential. On the other hand, these proteins may cause undesirable reactions inside the body′s cells. A full assessment of the safety of Naja ashei venom components for human cell application is still unknown. The aim of the study was to determine the effect of the exogenous application of three-finger toxins on the cells of monocytes (U-937) and promyelocytes (HL-60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The venom was reconstituted in distilled water and stored at −20 °C until use. Three-finger toxin (3FTx) fraction was purified using size-exclusion chromatography as described elsewhere [ 39 ]. Venoms from Naja nigricollis , Naja haje , Bitis arietans , and Dendroaspis polylepis were obtained from Baringo Snake Park, Kenya, in liquid form.…”
Section: Methodsmentioning
confidence: 99%
“…The venom was reconstituted in distilled water and stored at −20 °C until use. Three-finger toxin (3FTx) fraction was purified using size-exclusion chromatography as described elsewhere [ 39 ]. Venoms from Naja nigricollis , Naja haje , Bitis arietans , and Dendroaspis polylepis were obtained from Baringo Snake Park, Kenya, in liquid form.…”
Section: Methodsmentioning
confidence: 99%
“…B. arietans, N. ashei, and N. subfulva are snakes of medical importance in sub-Saharan Africa (Calvete et al, 2007;Currier, 2012;Tasoulis and Isbister, 2017;Onyango, 2018;Okumu et al, 2020;Dyba et al, 2021) (Figure 1). Antivenom is the mainstay of treatment for envenomation by these snakes but is expensive, has limited availability, and does not sufficiently neutralize some key venom toxins, e.g., cytotoxins which cause dermonecrosis in snake bite victims.…”
Section: Introductionmentioning
confidence: 99%
“…A PLA 2 and 3FTx rich protein fraction of NAV showed good antimicrobial activity against Staphylococcus epidermidis ( Bocian et al, 2020a ). Moreover, a study on the exogenous application of 3FTx from NAV on monocytes (U-937) and pro myelocytes (HL-60) and their effect on cell membranes reported that the mechanism of protein-lipid interactions depends on the presence of lipid polar parts and the degree of membrane saturation ( Dyba et al, 2021 ). Bocian and colleagues compared the protein concentration of venoms from Naja ashei and Agkistrodon contortix using the Pierce™BCA Protein Assay Kit, the 2-D Quant Kit, the Qubit® Protein Assay Kit, the Bradford Assay, and the Nanodrop method ( Bocian et al, 2020b ).…”
mentioning
confidence: 99%